The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1074/jbc.m601015200
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Esterase and Peptidase Activities of Acylaminoacyl Peptidase from Hyperthermophilic Aeropyrum pernix K1 by a Single Mutation

Abstract: It has been shown that highly conserved residues that form crucial structural elements of the catalytic apparatus may be used to account for the evolutionary history of enzymes. Using saturation mutagenesis, we investigated the role of a conserved residue (Arg 526 ) at the active site of acylaminoacyl peptidase from hyperthermophilic Aeropyrum pernix K1 in substrate discrimination and catalytic mechanism. This enzyme has both peptidase and esterase activities. The esterase activity of the wild-type enzyme with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
6
26
0
Order By: Relevance
“…Thus, 4-nitrophenyl caprylate is a good substrate for ApAAP (40). Table 2 shows that the values of k cat /K m for the mutant enzyme reactions diminished by 2 orders of magnitude.…”
Section: The Binding Strengths Of the Oligopeptide Are Similar For Thmentioning
confidence: 99%
“…Thus, 4-nitrophenyl caprylate is a good substrate for ApAAP (40). Table 2 shows that the values of k cat /K m for the mutant enzyme reactions diminished by 2 orders of magnitude.…”
Section: The Binding Strengths Of the Oligopeptide Are Similar For Thmentioning
confidence: 99%
“…The latter is the catalytic domain, which includes the active site and a Ser445-Asp524-His556 catalytic triad. Moreover, we found a conserved residue in the active site (Arg526) which plays a crucial role in catalysis and substrate discrimination (Wang et al, 2006). Saturation mutagenesis at this position had dramatic effects on esterase and peptidase activities.…”
Section: Introductionmentioning
confidence: 99%
“…Saturation mutagenesis at this position had dramatic effects on esterase and peptidase activities. Whereas the esterase activity of the wild type enzyme for p-nitrophenyl caprylate (pNP-C8) was 7 times higher than its peptidase activity for Ac-Leu-pnitroanilide, the esterase activities of mutants R526V and R526E were about 150-and 785-fold higher than their peptidase activities, respectively, using the same substrates (Wang et al, 2006). Further characterization showed that the mutants possessed hydrolytic activity towards a wide range of p-nitrophenyl alkanoate esters, with optimal acyl chain lengths ranging from C4 to C8.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations